2017
DOI: 10.3171/2016.2.jns152345
|View full text |Cite
|
Sign up to set email alerts
|

Body habitus, serum albumin, and the outcomes after craniotomy for tumor: a National Surgical Quality Improvement Program analysis

Abstract: OBJECTIVE Although there is a growing body of research highlighting the negative impact of obesity and malnutrition on surgical outcomes, few studies have evaluated these parameters in patients undergoing intracranial surgery. The goal of this study was to use a national registry to evaluate the association of body mass index (BMI) and hypoalbuminemia with 30-day outcomes after craniotomy for tumor. METHODS Adult patients who underwent craniotomy for tumor were extracted from the prospective National Surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Increased surgical site infections have been linked to body habitus and a recent series of 11,510 who underwent a craniotomy for tumor demonstrated that amongst WHO class I to III obese patients, the risk of surgical site infection was significantly higher. 40 Surgical site infection (SSI) is well known as a complication of smoking a recent series of 67,405 patients who underwent spinal surgery showed that smokers were at increased risk of SSI. 41 From our data, it is difficult to form a direct link between risk of 30-day readmission for SSI and smoking; however, smoking is an independent risk factor for SSI and overall numbers of smokers were higher in the readmissions group (35.7%) in our series compared with those not readmitted (20.8%).…”
Section: Complications Resulting 30-day Readmissionmentioning
confidence: 99%
“…Increased surgical site infections have been linked to body habitus and a recent series of 11,510 who underwent a craniotomy for tumor demonstrated that amongst WHO class I to III obese patients, the risk of surgical site infection was significantly higher. 40 Surgical site infection (SSI) is well known as a complication of smoking a recent series of 67,405 patients who underwent spinal surgery showed that smokers were at increased risk of SSI. 41 From our data, it is difficult to form a direct link between risk of 30-day readmission for SSI and smoking; however, smoking is an independent risk factor for SSI and overall numbers of smokers were higher in the readmissions group (35.7%) in our series compared with those not readmitted (20.8%).…”
Section: Complications Resulting 30-day Readmissionmentioning
confidence: 99%
“…In central nervous system, preoperative hypoalbuminemia affected the prognoses of patients with glioblastomas 13,14 . Hypoalbuminemia is also associated with increased odds of mortality and a nonroutine hospital discharge 7,8 , and is a risk factor for postoperative acute kidney injury in patients who underwent craniotomy for tumor 9 . In addition, hypoalbuminemia is independent predictor of extended hospital stay following brain tumor surgery 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is associated with poor postoperative outcomes and complications in patients underwent surgical intervention, such as cardiac 1,2 , hand 3 , colorectal cancer surgery 4 and orthopedic surgery 5,6 . In central nervous system, hypoalbuminemia is also associated with increased odds of mortality and a nonroutine hospital discharge 7,8 , and is a risk factor for postoperative acute kidney injury in patients who underwent craniotomy for tumor 9 . In addition, hypoalbuminemia is independent predictor of extended hospital stay following brain tumor surgery 10 .…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…Male gender, Hispanic ethnicity, and medium bed size were predictive for PE, whereas chronic heart failure was predictive for DVT [ 3 ]. Other predictors of postoperative VTE identified in the broader group of brain tumor patients were higher BMI, hypertension, functional dependence, lower Karnofsky Performance Scale (KPS) score, motor deficits, ventilator dependence, steroid usage, preoperative sepsis, longer operative times, and higher World Health Organization (WHO) tumor grade [ 11 , 40 , 42 , 43 , 46 ].…”
Section: Discussionmentioning
confidence: 99%